DESIGN AND IMPLEMENTATION OF UNIFIED MANAGEMENT SYSTEM FOR TEACHING ARABIC LANGUAGE IN MA’HAD AL-BIRR UNDER SUPERVISION OF ASIA MUSLIM CHARITY FOUNDATION - Muhammad Ali Bakri (Balai Penelitian dan Pengembangan Agama Makassar, 2019)
A management system has to be developed to suit the current situation in Indonesia, which would efficiently and effectively promote and educate Arabic Language and Islamic Studies for students. Improvement of management system of the Ma'had (Islamic boarding school) is a must, and following it is a necessity. The Government has Islamic Universities for Indonesian Muslims, same as it has for other religions. However, the Islamic Universities are very weak, even people who are graduating from Arabic Language faculty with a high grade do not know how to speak fluently in Arabic. Therefore, it is necessary to study how to develop a unified college management system to be implemented in each college. Qualitative research approach was applied to answer the research question. This study was conducted in Ma’had Al-Birr–Muhammadiyah University of Makassar, South Sulawesi, Indonesia. Observation and depth interview were applied to collect data. Some document analysis was employed to clarify the interview and observation data. This article is to describe education management system has been developed to achieve excellence in teaching Arabic Language and proper Islamic studies as per Quran and Hadith in the Ma’had Al-Birr Unismuh Makassar under the control and supervision of AMCF (Asia Muslim Charity Foundation). Some learning design have been taken are unified syllabus to be taught in all the college; an equally qualified staff to be employed; easy centralized supervision and control over all the college; unified academic calendar to be formulated for every academic year and formulating a single board for preparing the unified tests for all the college. This is one of the primary steps AMCF is taking now, with the vision of having a network of college, providing best possible learning opportunities and facilities in general, and scholars in particular, to learn Arabic Language and Islamic Studies. The AMCF future vision is to increase the number of qualified Scholars and Teachers in Indonesia, so that in turn, those scholars and teachers could contribute to solve the social problems in Indonesia by providing proper guidance to the public.